A novel paranormed sequence space derived by Schröder conservative matrix - Dağlı, M.C. (Carpathian Mathematical Publications, 2025)
In this paper, we offer a new paranormed sequence space $\ell(\tilde{S},p)$ by utilizing the Schröder conservative matrix and show that this new space is linearly isomorphic to $\ell(p).$ Moreover, we give its Schauder basis and determine some special duals such as $α$-, $β$-, $γ$-duals.